2011
DOI: 10.1259/bjr/21946513
|View full text |Cite
|
Sign up to set email alerts
|

The corpus callosum: white matter or terra incognita

Abstract: The corpus callosum is the largest white matter structure in the brain, consisting of 200-250 million contralateral axonal projections and the major commissural pathway connecting the hemispheres of the human brain. The pathology of the corpus callosum includes a wide variety of entities that arise from different causes such as congenital, inflammatory, tumoural, degenerative, infectious, metabolic, traumatic, vascular and toxic agents. The corpus callosum, or a specific part of it, can be affected selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…The corpus callosum (CC) is the largest portion of white matter in the human brain; it is located at its center between the right and left hemispheres and is responsible mainly for inter-hemispheric communication [5]. Morphological, electrophysiological, and neurophysiological studies have suggested alterations in the CC of schizophrenia patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The corpus callosum (CC) is the largest portion of white matter in the human brain; it is located at its center between the right and left hemispheres and is responsible mainly for inter-hemispheric communication [5]. Morphological, electrophysiological, and neurophysiological studies have suggested alterations in the CC of schizophrenia patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This results from the preponderance of neurons in the ATL [17], whereas glial cells and neuronal axons are more predominant in the CC [18]. It is important to compare proteomic profiles of these two regions of the brain mainly because this gives a more integrated view of brain function and not only what happens only with the neurons, as is typical of most other brain proteomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Major portion of the corpus callosum receives its arterial supply from the carotid system except for splenium, which is supplied by the vertebrobasilar system [14]. MRI is currently the most sensitive diagnostic tool as well as to monitor the evolution toward partial or total regression [11,15].…”
Section: Hyperintense Rims and Hypointense Cores On Flair Imagesmentioning
confidence: 99%